Legal Consequences of a Cessie Deed with a Guarantee Object Whose Term Has Expired - Rochma, Ainur; Navisa, Fitria Dewi; Sunardi, Sunardi (Hang Tuah Law Journal, 2025)
In the Indonesian legal system, cession is a transfer of rights to receivables or obligations made by a creditor to another party without the consent of the debtor. In practice, cession often involves collateral objects in the form of Mortgage Rights, such as Right to Cultivate Certificates (HGB). However, legal issues arise when the collateral object, namely HGB, has expired. In this case, the recipient of the cession needs to understand the legal consequences that arise in connection with the cession deed involving HGB whose validity period has expired. The purpose of this study is to analyze and explain the legal consequences for the recipient of the cession against the cession deed that includes collateral objects in the form of HGB whose validity period has expired. This study uses a normative legal research method. The results of the study on the legal consequences for the recipient of the cession against the cession deed with the collateral object of the building use rights certificate whose term has expired is that the deed is still considered valid and the new creditor still obtains the right to collect it, but the building use rights cannot be used as collateral by the new creditor and the collateral object cannot be registered with the land office because the term of the building use rights has expired and the legal efforts that can be taken by the recipient of the cession against the cession deed with the collateral object of the Right to Cultivate Certificate Mortgage whose term has expired are to negotiate with the old creditor regarding the cession deed by requesting accountability from the old creditor to renew or extend the term of the building use rights whose term has expired.